A real options approach to the baseball game betting - Shin-yun Wang (Economics & Finance Research, 2013)
Applications of real options can be found in real assets, but not in sports. This article proposes the real options model and applies it to baseball games, allowing the option to switch between the two teams during the game. We believe this is the first attempt to apply the switching options to the baseball game scheme. To do so, we first design some rules in our assumptions and define variables that are relevant to the baseball options. We combine features of the wager volatility and options to determine the optimal time of team switching, and we find that with low switching cost, the expected investment costs fall and so does risk. The application of switching options to baseball game also presents a feasible method to other sport games.
Keywords: 330